Design of Customized Mouthguards with Superior Protection Using Digital-Based Technologies and Impact Tests - Naser Nasrollahzadeh; Dominique P. Pioletti; Martin Broome (SpringerOpen, 2024)
Abstract Background In contact sports, an impact on the jaw can generate destructive stress on the tooth-bone system. Mouthguards can be beneficial in reducing the injury risk by changing the dynamics of the trauma. The material properties of mouthguards and their geometrical/structural attributes influence their protective performance. Custom-made mouthguards are the gold standard, and different configurations have been proposed to improve their protection and comfort. However, the effects of different design variables on the performance of customized mouthguards are not well understood. Results Herein, we developed a reliable finite element model to analyze contributing factors to the design of custom-made mouthguards. Accordingly, we evaluated the isolated and combined effect of layers' stiffness, thickness, and space inclusion on the protective capability of customized mouthguards. Our simulations revealed that a harder frontal region could distribute load and absorb impact energy through bending if optimally combined with a space inclusion. Moreover, a softer layer could enlarge the time of impact and absorb its energy by compression. We also showed that mouthguards present similar protection with either permanently bonded or mechanically interlocked components. We 3D-printed different mouthguards with commercial resins and performed impact tests to experimentally validate our simulation findings. The impact tests on the fabricated mouthguards used in this work revealed that significantly higher dental protection could be achieved with 3D-printed configurations than conventionally fabricated customized mouthguards. In particular, the strain on the impacted incisor was attenuated around 50% more with a 3D-printed mouthguard incorporating a hard insert and space in the frontal region than a conventional Playsafe® Heavypro mouthguard. Conclusions The protective performance of a mouthguard could be maximized by optimizing its structural and material properties to reduce the risk of sport-related dental injuries. Combining finite element simulations, additive manufacturing, and impact tests provides an efficient workflow for developing functional mouthguards with higher protectiveness and athlete comfort. We envision the future with 3d-printed custom-mouthguards presenting distinct attributes in different regions that are personalized by the user based on the sport and associated harshness of the impact incidences.